The contribution of drug resistant cancer stem cells to paediatric brain tumours - Punjaruk, Wiyada (2010)
Introduction: Recent studies have revealed that cancer stem cells (CSCs) exist in malignant disease. Additionally, it is proposed that these cells may survive following chemotherapy, and hence contribute to tumour relapse. A significant mechanism of drug resistance in CSCs is believed to be the expression of ATP-binding cassette (ABC) transporters that efflux cytotoxic agents out of cells. The objective of this study was to study the existence of CSCs in a panel of primary paediatric brain tumours (PBTs) and to determine if these were drug resistant via functional ABC transporters. Materials and Methods: The main cell lines characterised were: EPN-2 (primary ependymoma); MED-2 (recurrent medulloblastoma); SPNET-1 [primary CNS primitive neuroectodermal tumour (CNS PNET)]; and a commercial CNS PNET (PFSK-1). Basic characterisation of our cell lines were assessed by Telomeric Repeat Amplification Protocol (TRAP) assay, Terminal Restriction Fragments (TRF) assay, metaphase spread analysis and doubling time. To determine the proportion of cancer stem-like cells in the parental cell lines, CD133 and SOX2 co-staining immunofluorescence was performed and validated by Western blotting analysis. The expression of ABC transporters (ABCB1, ABCC1 and ABCG2) was also investigated by co-staining for CD133 and ABC transporters using immunofluorescence and Western blotting analysis. Flow cytometry was performed to examine ABCB1 function. Four clinically relevant drugs (etoposide, cisplatin, irinotecan and methotrexate) were used to assess the degree of drug resistance of these lines. Clonnogenic assay and neurosphere formation assay were then performed to investigate colony survival and the ability of cells to form neurospheres, respectively, after drug treatment. Finally, the potential to increase chemosensitivity by drug treatment in the presence of the ABCB1 inhibitor, Verapamil, was assessed. Results: Basic characterisation results demonstrated that a high level of telomerase activity and maintenance of telomere length was found in all cell lines (grown both as monolayers and neurospheres). Metaphase spread analysis showed a wide range of aberrant chromosome numbers in PFSK-1 cells whereas our cell lines demonstrated a more stable chromosome number. Neurospheres grew slower than monolayers and monolayers had constant growth rate with increasing passage number. It was found that for each cell line, a small subpopulation (8-12%) of cultured monolayer cells are positive for both CD133 and SOX-2 immunofluorescent staining whilst cultured neurospheres contained 35-45% of co-stained cells. No co-stained cells were identified in the commercial PFSK-1 line and these findings were consistent with the results from Western blotting analysis. Approximately 10% of the parental cell lines comprised cells co-expressing CD133 and ABCB1 or ABCC1 at a low level whilst none of our cell lines were positive for ABCG2. Additionally, the parental cell lines contained a small proportion of cells expressing functional endogenous ABCB1 (34±5.2% in EPN-2, 26.5±3.9% in MED-2 and 13.9±3.2% in SPNET-1). During multiple rounds of drug treatment, ABCB1 was consistently expressed at a high level throughout and the proportion of functional ABCB1 expressing cells increased in all cell lines almost 2 fold compared to the parental cell lines and the selected control sublines. Whilst ABCC1 expression was gradually upregulated after multiple rounds of treatment but ABCG2 expression remained negative. Drug combined with Verapamil treatment significantly decrease survival rate approximately 5 fold compared to drug treatment alone although the majority of surviving cells were still CD133 and ABCB1 positive. Conclusion: Newly established paediatric cell lines (EPN-2, MED-2 and SPNET-1) represented significant histological and biological features of the original tumours from which they were derived and were stable in standard culture condition for a prolonged period of time. The parental cell lines contained a small proportion of cells expressing endogenous functional ABCB1 at a low level indicating intrinsic drug resistance. After multiple rounds of drug treatment, ABCB1 was the major mechanism of drug resistance in our cell lines. ABCC1 were upregulated later in our cell lines after multiple rounds of drug treatment whereas none of our cell lines expressed ABCG2 during drug treatment.